FORMATION AND MANAGEMENT OF THE CLIENT BASE OF BANK - Azarenkova, Galyna; Janumyan , Edgar (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2021)
The relevance of the topic of the article is due to the fact that the priority of a modern commercial bank is the effective management of its own customer base through an effective customer policy. The profits that a commercial bank strives for are provided by the banking operations provided by the bank to its customers. Therefore, achieving this goal is impossible without the formation, maintenance and expansion of its own quality customer base. In addition, it is in a period of unstable economic situation, when there is a decline in income of Ukrainian consumers of banking services, inflationary expectations increase and distrust of financial institutions, the formation and implementation of effective customer policy of a commercial bank become particularly relevant. But the changing economic situation and the development of the banking business require further research in this area and the development of corrections in the current customer strategy of the bank. The subject of the research is the formation and management of the customer base of Ukrsibbank. The object of study is the economic relations that arise in the process of forming the customer base of the bank and its management. The purpose of the article is to identify scientific and methodological approaches and recommendations that will contribute to more effective management of the customer base of bank. The task of the work is to substantiate the division of the bank’s customer base into segments as an object of management in the bank. After analyzing the information obtained, it is possible to explore the conceptual basis for the formation of a customer base management system because the basics of its formation is an important step to make promising recommendations for the formation of strategies for establishing cooperation with different groups of customers. According to the results of the research, the existing scientific and methodological approaches to defining the customer base as an object of management in the bank are obtained. The conceptual bases of formation of the bank’s customer base management system are analyzed, give an opportunity to develop recommendations for the formation of strategies for establishing cooperation between the bank and various groups of customers. The obtained results can be used for future effective implementation of the customer-oriented management system in bank.